KAPPA KARAGINAN SEBAGAI BAHAN DASAR PEMBUATAN EDIBLE FILM DENGAN PENAMBAHAN PATI JAGUNG (MAIZENA) - Iva Ancewita Saragih; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of this research was to get the best formulation of kappa carrageenan as basic component of edible film with the addition of corn starch and to improve transparency and the rate of water transfer edible film. This research was conducted experimentally by using Completely Randomized Design (CRD) with factorial arrangement (4x3). The first factor was the concentration of corn starch (0; 2,5; 5 and 7,5g) and the second factor was kappa carrageenan concentration (0,6; 0,8 and 1 g). The result of variance analysis showed interaction of addition of corn starch and kappa carrageenan significantly affect edible film transparency. The addition of corn starch concentration gave significantly affect on thickness, water transfer, and transparency. The Addition of different carrageenan concentration gave significantly affect for thickness and water transfer. The best formulation according to characteristics of edible film was the J2K2 treatment which has thickness 0,144 mm, water transfer 0,055 g/hour and transparency 5,812. Keywords : edible film, corn starch, kappa carrageenan.